Translational pathway of a novel PFF2 respirator with chitosan nanotechnology: from the concept to the practical applications - Fleury Rosa, Mário Fabrício; Santos, Leonor Maria Pacheco; Grabois Gadelha, Carlos Augusto; Martins de Toledo, Aline; Carregaro, Rodrigo Luiz; Almeida da Silva, Ana Karoline; Mota da Costa, Lindemberg Barreto; Ferreira da Rocha, Adson; de Siqueira Rodrigues Fleury Rosa, Suélia (Frontiers in Nanotechnology, 2024)
Introduction: Translational Health Research (THR) is a tool aimed at assisting in the transformation of basic and/or applied scientific research into a health technology ready for commercialization. The aim of this study is to present the translational pathway in wich our research group developed a Personal Protective Equipment (PPE) called VESTA ® Facial Respirator with chitosan nanotechnology for protection against viruses, bacteria, and fungi. The aim of this study is to present the process of THR applied to a health technology research. Methods: The theoretical-methodological process of THR was applied to the Research and Development (R&D) of the respirator. This method is characterized by subsequent phases, as follow: T(0) -Concept, T(1) Pre-Clinical, T(2) Clinical, T(3) Industrial Scale Production, and T(4) Characterized by subsequent phases, as follow: Technological Evaluation. Results: Applying the THR process in the development and production of the Particulate Filtering Facepiece class 2 (PFF2) respirator with chitosan nanotechnology, University of Brasilia was able to transform the research idea into a respirator approved by the National Regulatory Agency for industrial-scale production within 24 months. The THR process is not a linear action; this flexibility allows essential activities for transforming research into a marketable product. Discussion: The integration among various stakeholders right from the genesis of research is a driving force for the effective utilization of results. The maturity of the country's industrial sector is crucial for converting university research into a marketable product, and governments need to prioritize these products in healthcare system incorporations. The academic culture of scientific research needs to intensify the technological 1 Fleury Rosa et al. transfer phase of its inventions. Conclusion: In less than 24 months, the University of Brasilia translated research on a new PPE into the market by applying the THR method.